Efforts to Improve Students' Attitudes with the Problem Based Learning Model - Roro Hoyi; Astalini Astalini; Dwi Agus Kurniawan (Universitas Pendidikan Ganesha, 2021)
There are still many students who have difficulty in learning physics subjects. This affects students' low physics learning outcomes. The purpose of this study is to analyze the problem-based learning model of physics. This type of research is classroom action research. This research was carried out in 2 cycles consisting of planning, implementing actions, observing, and reflecting. The test subjects were 15 students. The methods used to collect data are observation, interviews, questionnaires and tests. The instrument used to collect data is a questionnaire. The technique used to analyze the data is descriptive qualitative and quantitative analysis. The results of the study, namely the results of the study showed that in the first cycle the learning outcomes of students were 55%. While the second cycle of student learning outcomes of 80%. From these results, it can be concluded that physics learning outcomes can be improved through problem-based learning models. The implication of this research is that the problem-based learning model can be used by teachers in improving students' attitudes in learning.